Concurrent oocyte retrieval and hysteroscopy: a novel approach in assisted reproduction freeze-all cycles. Issue 2 (August 2016) - Ozgur, Kemal; Bulut, Hasan; Berkkanoglu, Murat; Humaidan, Peter; Coetzee, Kevin
Abstract: In this matched-controlled study ( n = 300), the effect of hysteroscopic surgery performed concurrently with oocyte retrieval on the reproductive outcomes of intracytoplasmic sperm injection (ICSI) freeze-all cycles was investigated in patients screened for intrauterine anomalies. Conventionally, hysterscopic surgery is performed in a different cycle from IVF, delaying treatment completion and increasing patient anxiety. One hundred and fifty patients who had hysteroscopic surgery concurrently with oocyte retrieval (hysteroscopy group) in ICSI freeze-all cycles were matched according to age and oocyte number with 150 ICSI freeze-all cycles, in which the patients required no hysteroscopy (control group). In the hysteroscopy group, hysteroscopy was performed for diagnostic ( n = 5) and therapeutic ( n = 145) purposes. Blastocyst culture and Cryotop vitrification was performed in both groups. Frozen embryo transfer (FET) was successfully performed in the hysteroscopy group from 35 days after oocyte retrieval. No significant differences were observed for implantation, pregnancy, clinical pregnancy and early pregnancy loss rates in the hysteroscopy and control groups (48.9%, 72.0%, 61.3% and 14.8% versus 48.3%, 75.3%, 64.7% and 14.3%, respectively). Performing hysteroscopic surgery concurrently with oocyte retrieval in a segmented-IVF programme has no negative impact on reproductive outcomes, increases efficiency, and provides patients with low-risk treatment.